A high-strength and high-flame-retardant magnesium alloy based on finite element simulation optimization and a preparation method thereof
Patent Information
- Application Number
- CN202611312975.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]但包括上述CN120843869A在内的现有超声改性技术,其工艺参数的筛选完全依赖于反复的实体铸造试错试验,存在以下固有缺陷:一方面,多批次对照试验导致研发周期长、原材料和电能损耗大;另一方面,试错法无法量化预判熔体内部的声流场分布及空化屏蔽效应,例如2kW高功率下熔体表层极易聚集空泡形成阻抗层导致能量传递失效,但现有技术仅凭定性经验无法提前识别此类无效区间
[0026]1、传统无模拟超声工艺需开展多组功率-时长对照试铸,原材料与电能损耗高,研发周期不低于15天。本发明通过ProCAST有限元模拟前置筛选,直接剔除无效工艺,仅需1组最优参数实体试验即可完成验证,研发周期缩短约70%,单次工艺优化电能消耗降低约32%。有限元模拟同时揭示了2kW高功率下空化屏蔽效应的量化机理。
Smart Images

Figure CN122979677A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnesium alloy preparation and metal forming technology, specifically to a strong, tough, and highly flame-retardant magnesium alloy based on finite element simulation optimization and its preparation method. Background Technology
[0002] AM50 cast magnesium alloy is widely used in lightweight components for new energy vehicles due to its low cost and excellent filling ability. Adding Ca to the AM50 matrix can generate a dense CaO / MgO composite oxide film on the melt surface, which significantly improves the alloy's ignition point and is the mainstream route for low-cost flame-retardant modification without rare earth elements.
[0003] However, when the Ca addition reaches 1.0 wt.% or more, coarse, continuous network-like Al2Ca and Al4Ca brittle intermetallic compounds will precipitate along the grain boundaries during the solidification stage of the alloy. This network phase completely cuts the α-Mg magnesium matrix, causing the alloy elongation to plummet from 11.7% of the matrix to about 1%, resulting in the performance contradiction of "high flame retardancy must be low plasticity".
[0004] To address this issue, existing technologies apply an ultrasonic field during the smelting process, utilizing the instantaneous high temperature and pressure generated by ultrasonic cavitation and the stirring effect of acoustic flow to break up the brittle network phase and refine the grains. For example, Chinese patent application CN120843869A discloses a composite process method for synergistically improving the flame retardant and mechanical properties of AM50 series magnesium alloys. This method involves applying ultrasonic treatment within a temperature range of 720℃ to 630℃, and then selecting the optimal parameter range of 1.5-2kW and 15-20min.
[0005] However, existing ultrasonic modification technologies, including CN120843869A mentioned above, rely entirely on repeated trial-and-error experiments in solid casting for the selection of process parameters, which has the following inherent defects: on the one hand, multiple batches of comparative experiments lead to long R&D cycles and large losses of raw materials and electrical energy; on the other hand, the trial-and-error method cannot quantitatively predict the acoustic flow field distribution and cavitation shielding effect inside the melt. For example, at a high power of 2kW, the surface of the melt is prone to accumulating cavitation bubbles to form an impedance layer, which leads to energy transfer failure. However, existing technologies cannot identify such invalid intervals in advance based solely on qualitative experience.
[0006] It is evident that the fundamental flaw in existing technologies lies in the lack of a numerical simulation method capable of pre-emptively quantifying and evaluating the effectiveness of ultrasonic process parameters, leading to low efficiency in process optimization and blind selection of parameters. Currently, there is no technical solution for pre-screening the ultrasonic process window for Ca-magnesium alloys using finite element simulation. Summary of the Invention
[0007] To address the shortcomings of existing ultrasonic treatment processes for Ca-containing magnesium alloys, which rely entirely on trial-and-error parameter selection and lack pre-quantitative evaluation methods, this invention provides a strong, tough, and highly flame-retardant magnesium alloy based on finite element simulation optimization and its preparation method.
[0008] This invention incorporates a ProCAST finite element simulation step before physical testing to quantitatively evaluate the melt flow field distribution and cavitation shielding risk under different ultrasonic powers. Based on this, the optimal process window is precisely identified, which in turn guides melting, gradient temperature controlled ultrasonic treatment, and casting molding, ultimately achieving a synergistic improvement in the alloy's high flame retardancy and excellent strength and plasticity.
[0009] To achieve the above objectives, this invention provides a method for preparing a strong, tough, and highly flame-retardant magnesium alloy based on finite element simulation optimization, comprising the following steps:
[0010] S1. Finite element simulation pre-optimization: Establish a three-dimensional model of the magnesium alloy melt and input the thermophysical parameters of the alloy melt; apply at least two sets of ultrasonic momentum sources with different powers to perform finite element simulation and obtain the melt flow field distribution data of the simulation output; based on the flow field distribution data, screen and determine the optimal process window for ultrasonic power and / or ultrasonic treatment time.
[0011] S2. Melting: Melting is carried out according to the composition ratio of magnesium alloy to obtain alloy melt.
[0012] S3. Ultrasonic treatment: Apply ultrasonic treatment to the alloy melt according to the optimal process window determined in S1.
[0013] S4. Casting: The ultrasonically treated alloy melt is cast into a mold to obtain a magnesium alloy.
[0014] Furthermore, the thermophysical parameters in S1 include the viscosity, density, and bulk modulus of the alloy melt; the finite element simulation uses ProCAST software, and the ultrasonic vibration is converted into the melt volume driving force through the Lighthill acoustic flow equivalent momentum source modeling method.
[0015] Furthermore, the process of selecting and determining the optimal process window in S1 includes:
[0016] By comparing the melt global flow field coverage under different power levels, the power range with flow blind zones is eliminated.
[0017] By comparing the cavitation distribution under different power levels, the power range with cavitation shielding layer is eliminated.
[0018] By comparing the flow field attenuation patterns under different ultrasonic treatment durations, the process intervals with ultrasonic treatment durations of 5 min and 25 min were eliminated.
[0019] Furthermore, the optimal process window in S1 is: ultrasonic power 1.5kW, ultrasonic treatment duration 20min, and ultrasonic treatment start and end temperature range of 660℃ to 630℃.
[0020] Furthermore, the smelting temperature in S2 is 720℃, and a CO2 / SF6 mixed protective gas with a volume ratio of 99:1 is introduced during the smelting process, and the slag is removed after holding at this temperature for 30 minutes.
[0021] Furthermore, in S3, a TC4 titanium alloy amplitude transformer is used for ultrasonic treatment. The amplitude transformer is preheated to 200°C and then vertically inserted into the melt to a depth of 1 / 2. The endpoint temperature of the ultrasonic treatment is 630°C, which corresponds to an alloy solidity of 10%. In S4, the casting is a bottom pouring method, and the mold is preheated to 200°C.
[0022] The present invention also provides a strong, tough, and highly flame-retardant magnesium alloy based on finite element simulation optimization, which is prepared by the above preparation method. By mass percentage, the magnesium alloy contains: Al 4.8% to 5.2%, Ca 1.15% to 1.25%, Mn 0.26% to 0.30%, and the balance is Mg.
[0023] Furthermore, the magnesium alloy has an average grain size ≤100μm, a second phase continuity ≤18%, and a basal texture strength ≤6MRD.
[0024] Furthermore, the magnesium alloy has an elongation of ≥9%, a tensile strength of ≥185MPa, and an ignition point of ≥825℃.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. Traditional ultrasonic simulation-free processes require multiple power-time comparison casting trials, resulting in high raw material and energy losses, and a development cycle of no less than 15 days. This invention uses ProCAST finite element simulation for pre-screening, directly eliminating ineffective processes. Verification can be completed with only one set of optimal parameter physical tests, shortening the development cycle by approximately 70% and reducing energy consumption per process optimization by approximately 32%. The finite element simulation also reveals the quantitative mechanism of the cavitation shielding effect under 2kW high power.
[0027] 2. After locking the optimal process window using finite element analysis, the average grain size of the alloy decreased sharply from 434.7 μm without ultrasonic matrix to 90.8 μm, a refinement of 79.1%. The originally continuous network of Al2Ca / Al4Ca brittle phases was broken into fine and dispersed particles. The equivalent diameter of the second phase was refined from 9.2 μm to 4.0 μm, and the continuity rate of the second phase decreased from 24.5% to 16.0%, a reduction of 34.7%, which significantly eliminated grain boundary stress concentration during deformation. The texture strength of the casting matrix decreased from 13.6 MRD to 4.9 MRD, the grain orientation became more uniform, and the deformation coordination ability was greatly improved.
[0028] 3. After processing with the optimal process of this invention, the alloy has a yield strength of 83.7 MPa, a tensile strength of 188.6 MPa, and an elongation of 9.2%. Compared with the AM50-1.2Ca matrix without ultrasonic treatment, the yield strength is increased by approximately 27%, the tensile strength by approximately 27.7%, the elongation increases from 4.0% to 9.2%, and the plasticity is increased by 73.6%. Tensile fracture characterization shows that the alloy of this invention has uniform dimples on the fracture surface and no large-area cleavage brittle surfaces, exhibiting typical ductile fracture characteristics.
[0029] 4. The Ca content is stably controlled at 1.15% to 1.25%, and the original ignition point of the alloy is 817℃. After the finite element optimization ultrasonic treatment of this invention, the Ca element is uniformly dispersed in the melt, with no local Ca-depleted areas. A complete and dense CaO / MgO composite oxide film can be formed on the surface, and the ignition point is increased to 830℃, which meets the safety standards for high-temperature components of new energy vehicles.
[0030] 5. This invention does not require the addition of rare earth elements, but only uses inexpensive Ca for micro-alloying modification; finite element simulation avoids ineffective high-power ultrasonic energy consumption, and the energy consumption of ultrasonic treatment of a single casting is reduced by about 28% in the mass production stage; bottom injection molding reduces the porosity and inclusion defects of castings, and improves the casting yield by about 12%. Attached Figure Description
[0031] Figure 1 Cloud maps showing melt flow velocity distribution under different ultrasonic powers;
[0032] Figure 2 Cloud maps showing melt flow velocity distribution under different ultrasonic treatment times;
[0033] Figure 3 The image shows the evolution of the second phase morphology in the AM50-1.2Ca alloy before and after ultrasonic treatment.
[0034] Figure 4 The evolution of the second phase morphology in AM50-1.2Ca alloy under different ultrasonic powers is shown in the figure.
[0035] Figure 5 The evolution of the second phase morphology in AM50-1.2Ca alloy under different ultrasonic times is shown in the figure.
[0036] Figure 6 The graph shows the variation of average grain size and texture intensity of AM50-1.2Ca alloy matrix under different ultrasonic powers.
[0037] Figure 7 The graph shows the variation of average grain size and texture intensity of AM50-1.2Ca alloy matrix under different ultrasonic times;
[0038] Figure 8The room temperature tensile stress-strain curves of AM50-1.2Ca alloy before and after ultrasound and the as-cast AM50 alloy are shown.
[0039] Figure 9 The effect of different ultrasonic powers on the mechanical properties of AM50-1.2Ca alloy under a fixed ultrasonic treatment time (20 min);
[0040] Figure 10 The effect of different ultrasonic times on the mechanical properties of AM50-1.2Ca alloy under a fixed ultrasonic power (1.5kW). Detailed Implementation
[0041] The preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used are commercially available; those not specifically sourced are commercially purchased products.
[0042] In the following embodiments and comparative examples, the raw materials used include: pure magnesium with a purity of ≥99.9%, pure aluminum with a purity of 99.7%, Mg-30Ca master alloy (where the Ca element content is 30±2%), and pure manganese with a purity of 99.5%, all of which are commercially available conventional materials.
[0043] The smelting equipment is a pit-type resistance furnace, equipped with a bottom-pouring gravity casting square metal mold. The ultrasonic treatment equipment is a Hangzhou Jinghao Machinery JHR2000W-20 ultrasonic melt treatment equipment, equipped with a 20kHz high-frequency transducer and a TC4 titanium alloy amplitude transformer (amplifier diameter is 16mm, length is 200mm).
[0044] Example
[0045] This embodiment provides a method for preparing a strong, tough, and highly flame-retardant magnesium alloy based on finite element simulation optimization, as well as the magnesium alloy prepared by this method.
[0046] I. Finite Element Simulation Pre-optimization
[0047] A three-dimensional model of the crucible-ultrasonic amplitude transformer was constructed using ProCAST software. In the model, the inner cavity of the crucible was simplified as a cylindrical container, and the ultrasonic amplitude transformer was inserted vertically into the melt to a depth of 1 / 2. The Lighthill acoustic flow equivalent momentum source modeling method was used to convert ultrasonic vibration into a volumetric driving force of the melt. Simulations were performed using three sets of ultrasonic momentum sources: 1.0kW, 1.5kW, and 2.0kW. In other embodiments, only two sets of different powers (e.g., 1.0kW and 1.5kW, or 1.5kW and 2.0kW) can be applied for simulation comparison, as long as the differences in the simulated flow field distribution data can be used to determine the optimal process window. Increasing the number of simulation power sets helps to more precisely locate the optimal power range, but it is not necessary for implementing this invention. Before simulation, the thermophysical parameters of the AM50-1.2Ca alloy melt, including melt viscosity, density, and bulk modulus, need to be input. These parameters are calculated using JMatPro software. The propagation speed of ultrasound in AM50-1.2Ca melt was set to c = 3981.178 m / s.
[0048] After the simulation is completed, the melt flow velocity distribution cloud map under different ultrasonic powers is output, such as... Figure 1 As shown. Figure 1 In the figure, (a) shows the flow velocity distribution of the molten pool without ultrasonic treatment. At this time, the maximum melt flow velocity of the molten pool is only 0.0852 m / s. There is only weak natural convection at the edge of the crucible. There is basically no flow in the central area of the molten pool, and the network second phase cannot be broken at all.
[0049] Figure 1 In the middle, (b) is the flow velocity distribution of the molten pool when ultrasonic treatment is performed at 1.0kW / 20min. At this time, the maximum flow velocity increases to 0.4639m / s, but there is a large flow blind zone at the bottom of the molten pool, the acoustic flow coverage is insufficient, and the second phase is not fully broken.
[0050] Figure 1 In the figure, (c) shows the flow velocity distribution of the molten pool during ultrasonic treatment at 1.5kW / 20min. At this time, the maximum molten flow velocity reaches 0.553m / s, and the solid fraction is about 9.8% (corresponding to the critical breakage range). The entire molten pool is covered by a high-speed flow field with no dead flow angles. Furthermore, there is no cavitation shielding layer below the amplitude transformer, and the ultrasonic energy can reach the depths of the molten pool directly.
[0051] Figure 1 In the middle, (d) is the flow velocity distribution of the molten pool during ultrasonic treatment with 2.0kW / 20min. The theoretical peak flow velocity can reach 0.636m / s, but a high-density cavitation group is generated below the ultrasonic amplitude transformer, forming a high acoustic impedance shielding layer. In the middle and late stages of solidification (when the solid fraction is ≥65%), the flow velocity in the lower part of the molten pool decreases significantly, and the deep melt has almost no stirring effect, resulting in typical cavitation shielding failure.
[0052] With the ultrasonic power fixed at 1.5kW, the effects of ultrasonic treatment durations of 5 min, 20 min, and 25 min on the melt flow field were further simulated. The results are as follows: Figure 2 As shown.
[0053] Figure 2 In the middle, (a) is the flow velocity distribution of the molten pool during ultrasonic treatment at 1.5kW / 5min. The ultrasonic treatment cycle is short, and the flow field has been greatly attenuated at the solidification endpoint (solidity of about 63.5%), and the network phase is not completely broken.
[0054] Figure 2 In the figure, (b) shows the flow rate distribution of the molten pool during ultrasonic treatment at 1.5kW / 20min. When the temperature is reduced to 630℃ (solid fraction of about 10%), the complete global acoustic flow is still maintained, which is exactly the optimal dynamic window for the second phase breakage.
[0055] Figure 2 In the middle, (c) is the flow velocity distribution of the molten pool during ultrasonic treatment at 1.5kW / 25min. Long-term ultrasonic treatment leads to saturation of cavitation in the molten pool, and the flow field intensity decreases significantly in the later stage of solidification. The second phase after breakage undergoes local agglomeration and coarsening.
[0056] Through the above complete set of finite element quantitative simulations, four types of inefficient or ineffective processes, namely 1.0kW, 2.0kW, 5min, and 25min, can be directly screened out. Finally, 1.5kW and 20min are identified as the optimal ultrasonic process parameters, and the ultrasonic start and end temperature range is determined to be 660℃ to 630℃.
[0057] II. Alloy Smelting
[0058] The alloy composition was prepared according to the target composition, with the following mass fractions: Al 4.91%, Ca 1.17%, Mn 0.27%, and the balance being Mg. The raw materials used were pure Mg, pure Al, Mg-30Ca master alloy, and Mg-5Mn master alloy.
[0059] The above raw materials were fed into a pit-type resistance furnace, heated to 720℃ and held for 30 minutes. During the melting process, a CO2 / SF6 mixed protective gas with a volume ratio of 99:1 was introduced to prevent the alloy melt from oxidizing and burning off at high temperatures. After the holding period, mechanical slag removal was performed.
[0060] III. Gradient-temperature controlled ultrasonic treatment
[0061] The TC4 titanium alloy amplitude transformer was preheated to 200℃ and vertically inserted into the melt to a depth of 1 / 2 (approximately 15-20 mm from the bottom of the crucible). The ultrasonic equipment was turned on, and ultrasonic treatment was applied at a constant power of 1.5 kW. The melt was slowly cooled along with the furnace, and ultrasonic treatment continued until the melt temperature dropped to 630℃, with a total ultrasonic duration of 20 minutes. Thermodynamic calculations and DSC tests verified that the solid fraction of the alloy at 630℃ was approximately 10%, and finite element simulations determined that this range represents the optimal kinetic window for network phase fragmentation.
[0062] IV. Casting
[0063] Immediately after ultrasonic treatment, bottom-pouring casting is performed, and the metal mold is preheated to 200°C. The melt is smoothly filled into the mold through the bottom-pouring casting system, eliminating filling turbulence and reducing oxide entrapment. After natural cooling, AM50-xCa magnesium alloy is obtained.
[0064] V. Test Results
[0065] The magnesium alloy prepared in this embodiment was characterized by its microstructure and tested for its mechanical properties.
[0066] Microstructure analysis: The morphology of the second phase of the alloy was observed using a ZEISS EVO18 scanning electron microscope, such as... Figure 3 , Figure 4 , Figure 5 As shown; the matrix grain size and texture intensity were determined using electron backscatter diffraction (EBSD) technology, such as... Figure 6 , Figure 7 As shown.
[0067] Figure 3 A comparison of the morphology of the second phase in AM50-1.2Ca alloy before and after ultrasonic treatment. Figure 3 In the middle, (a) is the matrix alloy without ultrasonic treatment, where coarse, continuous network of Al2Ca / Al4Ca brittle phases completely cover the grain boundaries, severely cutting the α-Mg matrix; Figure 3 In the example, (b) is an alloy treated with 1.5kW / 20min ultrasonication. The original continuous network of brittle phases was broken into fine and dispersed particles, which were evenly distributed within the grains and at the grain boundaries. The stress concentration at the grain boundaries was greatly eliminated.
[0068] Figure 4 To compare the morphology of the second phase under different ultrasonic powers when the ultrasonic treatment time is fixed at 20 min. Figure 4 In (a), the power output is 1 kW / 20 min, and the second phase still has a lot of continuous network structure, indicating insufficient fragmentation. Figure 4 In (b), the power is 1.5 kW / 20 min, and the network phase is fully broken into dispersed particles with uniform distribution; Figure 4In (c), the power is 2kW / 20min. The second phase shows local coarsening, and some areas still retain the network morphology, which proves that the high-power cavitation shielding effect leads to the failure of stirring.
[0069] Figure 5 To compare the morphology of the second phase under different ultrasound durations when the ultrasound power is fixed at 1.5kW. Figure 5 In (a), the ultrasonic treatment time was 1.5 kW / 5 min, which was insufficient. As a result, a large number of network phases were not broken and continued to be distributed along the grain boundaries. Figure 5 In (b), the power is 1.5 kW / 20 min, the network phase is fully broken up, and the dispersed particles are evenly distributed; Figure 5 In the case of (c), the power is 1.5 kW / 25 min. Prolonged ultrasound causes localized agglomeration and coarsening of the second-phase particles after fragmentation, resulting in uneven distribution.
[0070] Figure 6 To compare the matrix grain size and texture intensity under different ultrasonic powers when the ultrasonic treatment time is fixed at 20 min. Figure 6 In the middle, (a) 1kW / 20min corresponds to an average grain size of 133.6μm and a basal texture intensity of 9.2mRD; Figure 6 In the middle, (b) 1.5kW / 20min corresponds to an average grain size of 90.8μm and a basal texture intensity of 4.9mRD, which has the best grain refinement effect and the most significant texture weakening. Figure 6 In (c), 2kW / 20min corresponds to an average grain size of 167.9μm and a basal texture intensity of 14.6mRD. The grains are coarsened and the texture is enhanced.
[0071] Figure 7 To compare the matrix grain size and texture intensity under different ultrasound durations when the ultrasound power is fixed at 1.5kW. Figure 7 In the middle, (a) 1.5kW / 5min corresponds to an average grain size of 216.3μm and a basal texture intensity of 10.8mRD; Figure 7 In (b), 1.5 kW / 20 min corresponds to an average grain size of 90.8 μm and a basal texture intensity of 4.9 mRD.
[0072] The microstructure parameters of the magnesium alloy obtained in this embodiment were tested and found to be: average grain size 90.8 μm, equivalent diameter of the second phase 4.0 μm, continuity of the second phase 16.0%, and basal texture strength 4.9 mRD.
[0073] Mechanical property testing: Room temperature tensile tests were conducted using a universal testing machine. Tensile specimens were machined into dumbbell shapes with a total length of 64 mm and a gauge length of 22.5 mm. The gauge section cross-section dimensions were 5 mm × 3 mm. The displacement rate was 2 mm / min. The average value of three parallel specimens was taken under each condition. The tensile stress-strain curves are shown below. Figure 8As shown.
[0074] Figure 8 The table shows the room temperature tensile stress-strain curves of AM50-1.2Ca alloy before and after ultrasonic treatment, and the as-cast AM50 alloy. The AM50-1.2Ca matrix alloy without ultrasonic treatment exhibits an elongation of only 4.0%, showing obvious brittle fracture characteristics. After ultrasonic treatment with 1.5kW / 20min according to this invention, the elongation increases significantly to 9.2%, and the tensile strength increases simultaneously.
[0075] Figure 9 The effects of different ultrasonic powers (1kW, 1.5kW, 2kW) on the mechanical properties of AM50-1.2Ca alloy were investigated when the ultrasonic treatment duration was fixed at 20min. Figure 10 The effects of different ultrasonic durations (5 min, 20 min, 25 min) on the mechanical properties of AM50-1.2Ca alloy with a fixed ultrasonic power of 1.5 kW.
[0076] The mechanical properties obtained in this embodiment are: yield strength 83.7 MPa, tensile strength 188.6 MPa, and elongation 9.2%. Compared with the matrix without ultrasonic treatment, the yield strength is increased by about 27%, the tensile strength is increased by about 27.7%, the elongation is increased from 4.0% to 9.2%, and the plasticity is increased by 73.6%.
[0077] Flame retardant performance test: The ignition point of the alloy was determined using the vertical combustion method at a heating rate of 10℃ / min. The magnesium alloy obtained in this embodiment was found to have an ignition point of 830℃, meeting the safety standards for high-temperature components in new energy vehicles.
[0078] Phase analysis: X-ray diffraction (XRD) was used to analyze the phase composition of the alloy. The results showed that only three phases, α-Mg, Al2Ca, and Al4Ca, were present, with no new phases formed. This indicates that ultrasonic treatment only changed the morphology and distribution of the second phase, without altering the overall phase composition of the alloy.
[0079] Comparative Example 1
[0080] Comparative Example 1 is an AM50-1.2Ca alloy without ultrasonic treatment. Its composition is exactly the same as that of the Example (Al 4.91%, Ca 1.17%, Mn 0.27%, balance Mg). The melting and casting processes are exactly the same as those of the Example, except that ultrasonic treatment is not applied.
[0081] Testing revealed the following microstructure in this comparative example: average grain size 434.7 μm, second phase in a continuous network distribution with a continuity rate of 24.5%, and basal texture strength 13.6 mRD. Mechanical properties included an elongation of only 4.0% and an ignition point of 817℃. The tensile fracture surface exhibited typical brittle cleavage fracture characteristics, with numerous straight brittle cracks propagating along the network phase visible in the fracture morphology.
[0082] Comparative Example 2
[0083] Comparative Example 2 shows the ultrasonic treatment of AM50-1.2Ca alloy at 1kW / 20min, which was predicted to be an inefficient process by finite element analysis. Finite element simulation has shown a large flow blind zone at the bottom of the molten pool at this power (see...). Figure 1 (b) Insufficient sound flow coverage.
[0084] The physical experiment used the same alloy composition, smelting and casting process as the example, but the ultrasonic power was changed to 1.0kW. The other parameters (ultrasonic duration 20min, start and end temperature range 660℃ to 630℃) were the same as those in the example.
[0085] The microstructure of this comparative example was tested and found to be: average grain size 133.6 μm, second-phase equivalent diameter 4.7 μm, second-phase continuity 21.0%, and basal texture strength 9.2 mRD. The mechanical properties were: yield strength 80.3 MPa, tensile strength 175.5 MPa, and elongation 7.4%. Compared to the example, the grain size was coarsened by approximately 47%, and the elongation decreased by approximately 20%, demonstrating that the presence of a flow blind zone at 1 kW power resulted in insufficient second-phase fragmentation, leading to overall performance inferior to the digital optimization scheme of this invention.
[0086] Comparative Example 3
[0087] Comparative Example 3 shows an AM50-1.2Ca alloy subjected to 2kW / 20min ultrasonic treatment, which was predicted by finite element analysis to be a process of cavitation shielding failure. Finite element simulation has shown that at this power, a high-density cavitation cluster forms below the amplitude transformer, creating a high acoustic impedance shielding layer (see...). Figure 1 (d) The deep melt in the lower part of the molten pool has almost no stirring effect.
[0088] The physical experiment used the exact same alloy composition, smelting and casting process as the example, except that the ultrasonic treatment power was changed to 2.0kW, and the other parameters remained the same as those in the example.
[0089] The microstructure of this comparative example was determined to be: average grain size 167.9 μm, second-phase equivalent diameter 6.2 μm, second-phase continuity 22.5%, and basal texture strength 14.6 mRD. The mechanical properties were: yield strength 74.7 MPa, tensile strength 167.1 MPa, and elongation 6.9%. Compared to the example, the grains were significantly coarser, the texture was enhanced, and both strength and plasticity decreased simultaneously, demonstrating that the high-power cavitation shielding effect caused ultrasonic energy transfer failure, making it impossible to achieve microstructure refinement and performance improvement.
[0090] Comparative Example 4
[0091] Comparative Example 4 shows an AM50-1.2Ca alloy subjected to ultrasonic treatment at 1.5 kW / 5 min, which was predicted by finite element analysis to be a short-duration and inefficient process. Finite element simulations have shown that the flow field significantly decreases at the solidification endpoint (solidity approximately 63.5%) at this duration (see...). Figure 2 (a) The ultrasonic treatment cycle is insufficient to cover the optimal breakage window.
[0092] The physical experiment used the exact same alloy composition, smelting and casting process as the example, except that the ultrasonic treatment time was changed to 5 minutes, and the other parameters remained the same as the example.
[0093] The microstructure of this comparative example was as follows: average grain size 216.3 μm, equivalent diameter of the second phase 7.8 μm, second phase continuity 20.1%, and basal texture strength 10.8 mRD. The mechanical properties were: yield strength 79.8 MPa, tensile strength 148.4 MPa, and elongation 4.3%. Compared to the example, the elongation decreased by more than 53%, and a large amount of network-like second phase remained, demonstrating that insufficient ultrasonic treatment duration resulted in inadequate second phase fragmentation and extremely limited improvement in plasticity.
[0094] Table 1: Summary Comparison of Performance of Comparative Examples and Embodiments
[0095] process parameters No ultrasonic substrate 1kW / 20min 1.5kW / 20min (This invention) 2kW / 20min 1.5kW / 5min Average grain size (μm) 434.7 133.6 90.8 167.9 216.3 Second phase equivalent diameter (μm) 9.2 4.7 4.0 6.2 7.8 Second phase continuity rate (%) 24.5 21.0 16.0 22.5 20.1 Base texture intensity (MRD) 13.6 9.2 4.9 14.6 10.8 Yield strength (MPa) — 80.3 83.7 74.7 79.8 Tensile strength (MPa) — 175.5 188.6 167.1 148.4 Elongation (%) 4.0 7.4 9.2 6.9 4.3 Ignition point (°C) 817 — 830 — —
[0096] As shown in the table above, all ultrasonic processes (1kW / 20min, 2kW / 20min, 1.5kW / 5min) that were not screened by ProCAST finite element pre-simulation exhibited significantly inferior microstructure and mechanical properties compared to the digital optimization scheme of this invention. Finite element simulation is an essential distinguishing technical feature of this invention. By quantifying the flow field, predicting cavitation shielding, and accurately matching the solidification critical window, it achieves a synergistic improvement in flame retardancy and strong plasticity, solving the industry pain points of high trial-and-error costs and low performance limits of existing ultrasonic processes.
[0097] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing a strong, tough, and highly flame-retardant magnesium alloy based on finite element simulation optimization, characterized in that, Includes the following steps: S1. Finite element simulation pre-optimization: Establish a three-dimensional model of AM50-xCa magnesium alloy melt and input the thermophysical parameters of the alloy melt; apply at least two sets of ultrasonic momentum sources with different powers to perform finite element simulation and obtain the melt flow field distribution data of the simulation output; based on the flow field distribution data, screen and determine the optimal process window for ultrasonic power and / or ultrasonic treatment time; S2. Melting: Melt according to the composition ratio of AM50-xCa magnesium alloy to obtain alloy melt; S3. Ultrasonic treatment: Apply ultrasonic treatment to the alloy melt according to the optimal process window determined in S1; S4. Casting: The ultrasonically treated alloy melt is cast into shape to obtain AM50-xCa magnesium alloy.
2. The preparation method according to claim 1, characterized in that, The thermophysical parameters mentioned in S1 include the viscosity, density, and bulk modulus of the alloy melt; the finite element simulation uses ProCAST software and the Lighthill acoustic flow equivalent momentum source modeling method to convert ultrasonic vibration into melt volume driving force.
3. The preparation method according to claim 1, characterized in that, The screening to determine the optimal process window mentioned in S1 includes: By comparing the melt global flow field coverage under different power levels, the power range with flow blind zones is eliminated. By comparing the cavitation distribution under different power levels, the power range with cavitation shielding layer is eliminated. By comparing the flow field attenuation patterns under different ultrasonic treatment durations, the process intervals with ultrasonic treatment durations of 5 min and 25 min were eliminated.
4. The preparation method according to claim 1, characterized in that, The optimal process window described in S1 is: ultrasonic power 1.5kW, ultrasonic treatment duration 20min, and ultrasonic treatment start and end temperature range of 660℃ to 630℃.
5. The preparation method according to claim 1, characterized in that, The smelting temperature described in S2 is 720℃. During the smelting process, a CO2 / SF6 mixed protective gas with a volume ratio of 99:1 is introduced, and the temperature is maintained for 30 minutes to remove slag.
6. The preparation method according to claim 1, characterized in that, In S3, an ultrasonic treatment is performed using a TC4 titanium alloy amplitude transformer. The amplitude transformer is preheated to 200°C and then vertically inserted into the melt to a depth of 1 / 2. The endpoint temperature of the ultrasonic treatment is 630°C, which corresponds to an alloy solidity of 10%. In S4, the casting is a bottom-pouring casting, and the mold is preheated to 200°C.
7. A high-strength, high-flame-retardant magnesium alloy based on finite element simulation optimization, prepared by the preparation method according to any one of claims 1 to 6, characterized in that, The magnesium alloy comprises, by mass percentage: Al 4.8%–5.2%, Ca 1.15%–1.25%, Mn 0.26%–0.30%, with the balance being Mg.
8. The high-strength, high-flame-retardant magnesium alloy based on finite element simulation optimization according to claim 7, characterized in that, The magnesium alloy has an average grain size ≤100μm, a second phase continuity ≤18%, and a basal texture strength ≤6MRD.
9. The high-strength, high-flame-retardant magnesium alloy based on finite element simulation optimization according to claim 7, characterized in that, The magnesium alloy has an elongation of ≥9%, a tensile strength of ≥185MPa, and an ignition point of ≥825℃.
Citation Information
Patent Citations
Composite process method for synergistically improving flame retardant property and mechanical property of AM50 magnesium alloy
CN120843869A